2011
DOI: 10.1002/ajim.20952
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk by occupation and industry: Analysis of the CECILE study, a population‐based case–control study in France

Abstract: These findings suggest a possible role of occupational exposures in breast cancer, including night-shift work, solvents and endocrine disrupting chemicals and require further studies with detailed assessment of occupational exposures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 53 publications
(53 reference statements)
0
44
0
1
Order By: Relevance
“…11 14-17 19 The gradient of high risk of breast cancer in occupational sectors with a high socioeconomic position (white collar) and low risk in low socioeconomic occupations (blue collar) has been reported in several previous studies. [10][11][12][13][14][15][16][17][18] Even if some of the excess risk is due to reproductive and lifestyle factors as the adjustments show, many studies, like ours, still detect a high risk for this group even after adjustments. A potential alternative explanation has been put forward by Pudrovska et al who discussed the life-course stress approach, where occupations with a high socioeconomic position have a higher level of job authority and are therefore more stressful.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…11 14-17 19 The gradient of high risk of breast cancer in occupational sectors with a high socioeconomic position (white collar) and low risk in low socioeconomic occupations (blue collar) has been reported in several previous studies. [10][11][12][13][14][15][16][17][18] Even if some of the excess risk is due to reproductive and lifestyle factors as the adjustments show, many studies, like ours, still detect a high risk for this group even after adjustments. A potential alternative explanation has been put forward by Pudrovska et al who discussed the life-course stress approach, where occupations with a high socioeconomic position have a higher level of job authority and are therefore more stressful.…”
Section: Discussionmentioning
confidence: 55%
“…All of them found that the reproductive and lifestyle factors explained only a minor part or no part of the difference between occupational groups. 11 14-17 19 However, one study only looked at premenopausal breast cancer, 19 some studies did not adjust for alcohol consumption [14][15][16] or physical activity, [14][15][16][17] and two studies lacked data on breast feeding 14 16 and HRT. 14 17 In addition, several studies had a case-control design, which increased the risk of biases such as recall bias.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…In a French case-control study on occupation as a risk factor for breast cancer, an OR of 1.4 (CI 0.9 to 2.1) emerged for women employed for more than 10 years as nurses. An overall OR of 2.4 (CI 0.9 to 6.0) was reported in textile workers and 1.5 (CI 0.9 to 2.6) in tailors/dressmakers, with no information available on working time schedules of these occupational groups (26). In a nested case-control study from a cohort of Danish nurses, signifi cantly increased ORs ranging between 1.8 and 2.9 were found when work after midnight was compared with permanent day work (27).…”
Section: Studies Since the Iarc Assessmentmentioning
confidence: 95%
“…This database contains a continuously updated set of information on the subjects of national economy, with the activities of the enterprises encoded according to the Polish Classification of Activities (Polska Klasyfikacja Działalności -PKD) further studies was expressed as follows: "more studies are needed to examine this potential risk in other professions and for other cancers" (Dr Cogliano, Head of the IARC Monographs Programme) [2,3]. Over the past 5 years, eight additional epidemiological studies have been reported, including: three investigations in nurses: a Norwegian nested case-control study on breast cancer [4], a Danish nested case-control study on breast cancer [5], an ovarian cancer in Nurses Health Study [6], as well as a breast cancer case-control study in Germany [7], and France -breast cancer case-control CECILE study [8], industrial males cohort in Japan -a study on prostate cancer [9], and females in China -a study on breast cancer [10]. Moreover, one registry-based linkage study was conducted in Scandinavian countries [11].…”
Section: Methodsmentioning
confidence: 99%